Induction Therapy With Antithymocyte Globulin and Delayed Calcineurin Inhibitor Initiation for Renal Protection in Liver Transplantation: A Multicenter Randomized Controlled Phase II-B Trial. Issue 5 (27th July 2021) - Nair, Amit; Coromina Hernandez, Laia; Shah, Shimul; Zervos, Xaralambos; Zimmerman, Michael; Sasaki, Kazunari; Diago, Teresa; Hashimoto, Koji; Fujiki, Masato; Aucejo, Federico; Bollinger, Jessica; Kaiser, Tiffany L.; et al.
Abstract : Background: Calcineurin inhibitor (CNI)-based immunosuppression in liver transplantation (LTx) is associated with acute and chronic deterioration of kidney function. Delaying CNI initiation by using induction rabbit antithymocyte globulin (rATG) may provide kidneys with adequate time to recover from a perioperative insult reducing the risk of early post-LTx renal deterioration. Methods: This was an open-label, multicenter, randomized controlled clinical trial comparing use of induction rATG with delayed CNI initiation (d 10) against upfront CNI commencement (standard of care [SOC]) in those patients deemed at standard risk of postoperative renal dysfunction following LTx. The primary endpoint was change in (delta) creatinine from baseline to month 12. Results: Fifty-five patients were enrolled in each study arm. Mean tacrolimus levels remained comparable in both groups from day 10 throughout the study period. A significant difference in delta creatinine was observed between rATG and SOC groups at 9 mo ( P = 0.03) but not at month 12 ( P = 0.05). Estimated glomerular filtration rate levels remained comparable between cohorts at all time points. Rates of biopsy-proven acute rejection at 1 y were similar between groups (16.3 versus 12.7%, P = 0.58). rATG showed no significant adverse effects. Survival at 12 mo was comparable between groups ( P = 0.48). Conclusions: Although the use of induction rATG and concurrent CNI deferral in this study did not demonstrate a significant difference in delta creatinine at 1 y, these results indicate a potential role for rATG in preserving early kidney function, especially when considered with CNI deferral beyond 10 d or lower target tacrolimus levels, with acceptable safety and treatment efficacy.